High-Spatial-Resolution - Nemchin, Alexander; Horstwood, Matthew; Whitehouse, Martin (ELSEVIER SCI LTD, 2013)
High-spatial-resolution isotope analyses have revolutionised U–(Th–)Pb geochronology. These analyses can be done at scales of a few tens of microns or less using secondary ion mass spectrometry or laser ablation inductively coupled plasma mass spectrometry. They allow determination of the internal age variation of uranium- and thorium-bearing minerals and as a consequence much greater understanding of Earth system processes. The determination of variation on the micron scale necessitates the sampling of small volumes, which restricts the achievable precision but allows discrimination of discrete change, linkage to textural information, and determination of multiple isotopic and elemental data sets on effectively the same material. High-spatial-resolution analysis is being used in an increasing number of applications. Some of these applications have become fundamental to their scientific fields, while others have opened new opportunities for research.